2005
DOI: 10.1182/blood-2005-03-1004
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic marrow stromal cells are immune rejected by MHC class I– and class II–mismatched recipient mice

Abstract: It has been suggested that marrow stromal cells (MSCs) may be immunoprivileged and can engraft in allogeneic recipients with intact immune systems. We determined if the implantation of murine MSCs engineered to release erythropoietin (Epo) would be feasible in major histocompatibility complex (MHC)-mismatched allogeneic mice without immunosuppression, and we monitored hematocrit (Hct) as a reporter of MSC graft survival. MSCs from C57Bl/6 mice were engineered to release murine Epo (Epo ؉ MSCs) and implanted su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
425
2
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(450 citation statements)
references
References 60 publications
(83 reference statements)
18
425
2
5
Order By: Relevance
“…Allogeneic rodent MSCs are recognized by the host immune system in vivo, elicit a cellular and humoural immune response, and fail to induce tolerance in graft-versus-host disease (GVHD) (Badillo et al, 2008;Ringden and Le Blanc, 2011). When studied within a non-myeloablative allogeneic bone marrow (BM) transplantation setting in naive immune competent mice, infused allogeneic MSCs prime host T cells and induce a memory T-cell response, resulting in rejection of the BM graft (Eliopoulos et al, 2005;Nauta et al, 2006). This partial lack of immune competence has been attributed to defects in the expression of different components of antigen processing machinery by MSCs (e.g.…”
Section: In Vivo Graft Stem Cell Immunogenicitymentioning
confidence: 99%
“…Allogeneic rodent MSCs are recognized by the host immune system in vivo, elicit a cellular and humoural immune response, and fail to induce tolerance in graft-versus-host disease (GVHD) (Badillo et al, 2008;Ringden and Le Blanc, 2011). When studied within a non-myeloablative allogeneic bone marrow (BM) transplantation setting in naive immune competent mice, infused allogeneic MSCs prime host T cells and induce a memory T-cell response, resulting in rejection of the BM graft (Eliopoulos et al, 2005;Nauta et al, 2006). This partial lack of immune competence has been attributed to defects in the expression of different components of antigen processing machinery by MSCs (e.g.…”
Section: In Vivo Graft Stem Cell Immunogenicitymentioning
confidence: 99%
“…infusion of allogeneic MSC in humans has led to encouraging results in different human diseases including GVHD [15], breast cancer [71], osteogenesis imperfecta [72], metachromatic leukodystrophy and Hurler syndrome [73], hematological malignancies [74] and stroke [75]. However, recent in vivo experiments raised some doubts about the reported immunoprivilege of MSC, indicating that at least in some cases, administration of allogeneic MSC into an MHC-mismatched host may result in their rejection [19]. Similarly, infusion of allogeneic MSC in mice receiving an allogeneic BM transplantation did not prevent BM rejection as efficiently as in mice infused with autologous MSC [18].…”
Section: Msc-mediated Immunological Effects In Vivomentioning
confidence: 99%
“…Since these early reports, many studies have demonstrated that MSC affect the function of different immunocompetent cell types, lending support to their pioneering utilization in acute graft-versus-host disease (GVHD) [15] and providing the rationale for their possible use in the treatment of autoimmune disorders [16]. However, recent reports have stressed that the outcome of the interaction between MSC and immune cells is strongly influenced by environmental factors, possibly leading to conflicting results [17][18][19]. This review addresses the known effect of MSC on the immune system in light of their possible use in the treatment of immune-mediated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…31 After a rapid increase in hematocrit, the values returned to normal within 5 weeks after syngeneic transplantation. Allogeneic MSCs induced the formation of neutralizing anti-EPO antibodies with secondary anemia.…”
Section: Nonviral Gene Transfer Into Murine Mscsmentioning
confidence: 97%
“…21 Whereas the mechanisms leading to autoimmune responses are still unclear, there was no evidence that the EPO secreted by MSCs was the cause of the immune response. 31 Therefore, we hypothesized that the production of anti-EPO antibodies in the host might be associated with changes induced by the viral transduction of MSCs. However, our results refute this hypothesis, as nucleofected EPO-secreting MSCs also induced the production of antibodies against EPO and the second transgene, GFP, in immunocompetent mice.…”
Section: Nonviral Gene Transfer Into Murine Mscsmentioning
confidence: 99%